Elizabeth Bishop com Marianne Moore : um diálogo entre a singularidade e a tradição - Silva, Raínne Fogaça da (2023)
This thesis aims to investigate, based on selected poems from the books North & South (1946), by Elizabeth Bishop, and Selected Poems (1935), by Marianne Moore, singular and original aspects, as well as, on the other hand, common traits, belonging to a tradition, in the poetic creation of Bishop, poet who is direct heir of North American high modernism, side by side with Moore, a fundamental poet for understanding the period that, throughout the 1920s and 1930s, reconfigured the way of thinking and writing literature. The analysis carried out in a comparative movement, will take place, above all, from the effort employed by the poets in the imagery and rhythmic construction of their creations. This study, therefore, is constructed from three chapters: at first, the discussions that deal with the debate between rupture and tradition, the new and the old, from Leyla Perrone-Moisés (1998), Octavio Paz (1984) and T.S. Eliot (1989); in the second chapter, in turn, the debate surrounding the analysis supported by commentators of the authors' works, of the six poems selected for this thesis. In the third and last chapter, finally, the discussion is centered on the different meanings attributed to the words modernism, modern and modernity, from Antoine Compagnon (2014), mainly; and, in the second section, the focus is on the place Elizabeth Bishop and Marianne Moore occupy in the periods of late modernism and high modernism, respectively. As from the readings and analysis it is possible to state that, in Moore's case, the use of a more informal language is recurrent, based on impersonality, and the syllable break between the verses, supported, sometimes, by a rhythmic rigor, and in others by free verse; the precision with which she describes the images constructed in the poems is another characteristic element of the poet. In the case of Elizabeth Bishop's poetic work, what comes closest to Moore is the attention given to the delineation of the images, always described in detail by the lyrical subject in the analyzed poems. The point of greatest distance between the two poets, in turn, concerns their dealing with subjectivity and impersonality: while for Moore, as mentioned earlier, working with impersonality is essential in the poem, Bishop tends to break down the barrier that separates subjectivity from the impersonal, which causes tension in the poem itself.